Fictional representations of ethnicity, nationhood, and identity in Kwani? Journal and other Kwani trust publications - Ndago, Abenea Odhiambo (University of the Free State, 2020)
This study examines the representation of ethnicity, nationhood, and identity in Kwani? Journal, founded by the late Kenyan writer, Binyavanga Wainaina in 2002 through the sponsorship of the American Ford Foundation and other Western donors. The study specifically unpacks how ethnicity seems to influence the representation of Kenyan nationhood in some of the journal’s issues. The study engages in a close reading of the selected journal issues focusing on the Kenyan socio-political space between 2003 and 2015. It considers Kwani? Journal as a popular space where Kenyan politics and competing national ideologies regarding the history of the struggle for independence, statehood and ethnicity are mediated. In this regard, the study relies on relevant formulations on nationhood to investigate how specific Kwani? texts, such as short stories, poems, reportage, and contemporary paratexts, narrate the role of the Mungiki Cult during Kenya’s electoral contestations. Furthermore, the study examines how these texts use characterisation to represent different Kenyan ethnicities and discusses the ways in which the issue of ethnicity influences the journal’s treatment of the nature of Kenya’s different regimes. The study posits that ethnicity determines how Kwani? Journal represents ethnic and national violence, and thus, shows that the journal aligns with the Kenyan State metanarrative on ethnicity and political leadership. The study draws on relevant theorists of nationhood such as Anderson (1983), Bhabha (1990), and Renan (1990). It is also anchored on popular culture theory, specifically Barber (1987), Fabian (1997), and Mbembe’s (2001) theorisation of the subversive relationship between popular texts and State metanarratives. Moreover, the study incorporates varied scholarship on Kenyan nationhood, as represented by Ogot (2003), Ochieng (2009), Atieno-Odhiambo (2003), Anderson (2005), Elkins (2005), Hornsby (2013), and Kanyinga (2014). The study concludes that Kwani? Journal is not unique in its adoption of State metanarratives on ethnicity, nationhood, and national identity. The research notes further that the journal’s adoption of the narratives created by the ruling Kikuyu elite alludes to the ethnicised nature of the Kenyan socio-political space and re-enacts the popular cultures of different Kenyan communities along an ethnic interpretation of Kenya’s nationhood.
Thesis (Ph.D. (English))--University of the Free State, 2020
Keywords: Ethnicity; Nationhood; Identity; Kwani? Journal; Popular culture; Metanarratives